The Effectiveness of Learning to Write Conservation Poetry Texts with a Synectic Model Based on the Students’ Independence Level (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Poetry text writing skills possessed by students so that they can produce poetry based on freedom of imagination and creativity. Synectic learning model with the students’ independence level is appropriate for learning to write poetry. The purpose of this study is to analyze the effectiveness of learning to write poetry texts with a synectic model based on the independence level of the classroom students. This study used a quasi-experimental method with data collection techniques using observation and interview guides. Final data analysis used one-way ANOVA test to analyze differences in the effectiveness of learning to write conservation poetry texts based on the independence level. The results showed the average value of high independence students was 87.86, then the average independence learning outcomes were 84.63, while the average learning outcomes of low independence was 84. Learning to write conservation poetry texts with synectic models is more effective to be used in students who have a high level of independence. The benefits of the results of this study can add to the learning theory to write poetry that accustoms students’ independence more effectively.